Сучасні новації в системі мотиваційного менеджменту персоналу в контексті управління та адміністрування підприємств - Бочарова, Наталія Олександрівна; Бочарова, Наталья Александровна; Bocharova, Nataliia (My University, 2019)
UK: Стаття присвячена впровадженню сучасних новації в системі мотиваційного менеджменту персоналу; проаналізовано та обґрунтовано теоретичні аспекти оновлення механізму управління розвитком системи мотивації в контексті реалізації забезпечення ефективної дії концепції ділового адміністрування підприємств. EN: Formulation of the problem. In today's conditions, as never before, the leading role of work motivation in the production management system is formed. After all, it is the motivation of work is the dominant mechanism of influence on staff in order to form their need for highly productive work, increasing interest in improving the end results and ensuring the competitiveness of the enterprise, company, organization in domestic and global markets. Therefore, the issue of ensuring an effective system of staff motivation for highly efficient work in the context of management and administration of enterprises is extremely important. The purpose of the article is to study current trends and substantiate theoretical approaches to the formation of management strategies for the development of work motivation in the system of measures of business administration of enterprises in a transitive economy of Ukraine. Each evolutionary period is characterized by a dominant management style used to support growth, while each revolutionary period is characterized by a dominant management problem that must be addressed before growth can continue. Conclusions. Thus, given the fact that people, from the point of view of the economy, are an extremely valuable resource, which indicates the need to use them with maximum efficiency, we can offer for practical implementation in modern realities of the formation and operation of the vast majority of Ukrainian enterprises. management and administration of personnel on the basis of its comprehensive motivation as a friendly attitude of managers to all employees in the organization, the responsibility of managers at all levels for the successful operation of the organization, to munikatsiyi (horizontal and vertical) both inside and outside the organization, creating an atmosphere of openness, honesty, trust people, promotion of their talents and commitment to continuous improvement in both personal work and work organization.
Modern innovations in the system of motivational management of personnel in the context of management and administration of enterprises
Keywords: ділове адміністрування; механізм управління підприємствами; мотиваційний механізм; система мотивації праці; персонал; business administration; enterprise management mechanism; motivational mechanism; labor motivation system; personnel